MANAJEMEN PENGARSIPAN JARINGAN DOKUMENTASI DAN INFORMASI HUKUM (JDIH) KOMISI PEMILIHAN UMUM PROVISI JAWA TIMUR - Mahendra, Faiz Dzikri Ezza (JURNAL BISNIS KOLEGA, 2024)
The management of the Legal Documentation and Information Network (JDIH) of the East Java Provincial KPU began in July 2023, marked by the formation of a team based on the decision of the East Java Provincial KPU Number: 18/HK.03.1-Kpt/Prov/30/07/2023 concerning the composition of the Legal Documentation and Information Network (JDIH) team in the Bengkulu Provincial KPU. The Legal Documentation and Information Network is a decision on the management of legal documentation and information on technical guidelines for managing legal documentation and information within the KPU (Regency/City) to date, the number of legal products that have been uploaded to the JDIH of the East Java Provincial KPU from 2013 to 2021 is 191. The system used in the sub-section of technical implementation of elections, participation, public relations and human resources has been well-programmed. On the JDIH website of the East Java Provincial KPU, there are KPU regulations, decisions which include (Provincial KPU decisions and Regency/City KPU decisions). The data collection technique in this journal is obtained from literature and participatory activities in the East Java Provincial KPU office. The results obtained from this activity can determine the comparison of the number of viewers and the number of PKPU that have been established